Characterization of Thyroid Hormones Antivertigo Effects in a Rat Model of Excitotoxically-Induced Vestibulopathy - Bringuier, Claire M.; Hatat, Bérenice; Boularand, Romain; Chabbert, Christian; Tighilet, Brahim (Frontiers in Neurology, 2022)
Impaired vestibular function induces disabling symptoms such as postural imbalance, impaired locomotion, vestibulo-ocular reflex alteration, impaired cognitive functions such as spatial disorientation, and vegetative deficits. These symptoms show up in sudden attacks in patients with Ménière or neuritis and may lead to emergency hospitalizations. To date, however, there is no curative solution to these pathologies and the effectiveness of treatments used to reduce symptoms in the management of patients is discussed. Thus, elucidating the biological mechanisms correlated to the expression kinetics of the vestibular syndrome is useful for the development of potential therapeutic candidates with a view to relieving patients and limiting emergency hospitalizations. Recently, a robust antivertigo effect of thyroxine (T4) was demonstrated in a rodent model of impaired vestibular function induced by unilateral surgical section of the vestibular nerve. The aim of the present study was to assess thyroid hormones L-T4 and triiodothyronine (T3) as well as the bioactive thyroid hormone metabolite TRIAC on a rodent model of acute unilateral vestibulopathy more representative of clinical vestibular pathology. To this end, a partial and transient unilateral suppression of peripheral vestibular inputs was induced by an excitotoxic lesion caused by transtympanic injection of kainic acid (TTK) into the inner ear of adult rats. Vestibular syndrome and functional recovery were studied by semi-quantitative and quantitative assessments of relevant posturo-locomotor parameters. In contrast to the effect previously demonstrated in the complete and irreversible vestibular injury model, administration of thyroxine in the TTK rodent model did not display significant antivertigo effect. However, it is noteworthy that administration of thyroxine showed trends to prevent posturo-locomotor alterations. Furthermore, the results of the current study suggested that a single dose of thyroxine is sufficient to induce the same effects on vestibular syndrome observed with sub-chronic administration, and that reducing the T4 dose may more efficiently prevent the appearance of vestibular deficits induced by the excitotoxic type lesion. Finally, comparison of the antivertigo effect of T4 in different vestibulopathy models enables us to determine the therapeutic indication in which thyroxine could be a potential therapeutic candidate.